2005
DOI: 10.1203/01.pdr.0000151354.07752.9b
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Proximal Tubule Tight Junction Proteins

Abstract: We demonstrated previously that neonatal proximal tubules have a lower passive paracellular permeability to chloride ions and higher resistance than that of adult proximal tubules. In addition, administration of thyroid hormone to neonates, before the normal maturational increase in serum thyroid hormone levels, prematurely accelerates the developmental increase in chloride permeability to adult levels. To test the hypothesis that there is a maturational change in tight junction proteins and that thyroid hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…LTA binds to specific glycoproteins present only in proximal tubule brush border (apical) membranes. 35,36 We demonstrate that AM fractions isolated with LTA were enriched with villin, validating the isolation of the outer brush border membrane fraction. Our results show that intrarenal administration of fenoldopam increased the quantity of AT 2 R protein in these AMs.…”
Section: Salomone Et Al D 1 and At 2 Receptor Interactions In Natriursupporting
confidence: 67%
“…LTA binds to specific glycoproteins present only in proximal tubule brush border (apical) membranes. 35,36 We demonstrate that AM fractions isolated with LTA were enriched with villin, validating the isolation of the outer brush border membrane fraction. Our results show that intrarenal administration of fenoldopam increased the quantity of AT 2 R protein in these AMs.…”
Section: Salomone Et Al D 1 and At 2 Receptor Interactions In Natriursupporting
confidence: 67%
“…Claudin 2 is a cation-selective claudin (30), which may account for the higher P Na /P Cl measured in the PCT of neonates. Occludin, on the other had, has a fourfold greater expression in adult tubules than in neonate tubules (16). As speculation, it is possible that changes in claudin 2, occludin, or other proximal tubule tight junction proteins may account for the changes in paracellular properties found in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Claudin 2 and occludin have been identified as tight junction proteins in the proximal tubule (11,13,21,25). Using immunoblot and immunohistochemistry, we have found in the rat that claudin 2 has a fourfold greater abundance in neonate proximal tubules than in adult tubules (16). Claudin 2 is a cation-selective claudin (30), which may account for the higher P Na /P Cl measured in the PCT of neonates.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously shown that claudin 2 protein expression is fourfold greater in neonatal proximal tubules than in adult proximal tubules while occludin protein abundance increases during postnatal development using immunoblot analysis and immunohistochemistry in the rat (18). Claudin 2 has been shown to increase the permeability of sodium, and the high paracellular sodium-to-chloride permeability in neonates compared with adults may be explained by the high level of expression of this claudin (50).…”
Section: Discussionmentioning
confidence: 96%